Analytical methods comparison for soil organic carbon determination in Andean Forest of Sangay National Park-Ecuador (2017)
A relationship among total organic carbon content determined by ignition loss (LOI) and DUMAS combustion methods, were perfomed in evergreen Andean eyebrow forest soils, southwestern zone of Sangay National Park- Ecuador, where three conglomerates were established as follows: (C) with five plots (P) with plots of 20 x 20 m. In each plot, five digging trenches and four soil samples were carried out at different depths: 0-10, 10-20, 20-30 and 30 cm, respectively. It is observed that the amount of total organic carbon obtained by the DUMAS and LOI method (R2 = 0.99) does not differ significantly. However, the DUMAS total organic carbon determination methodology showed greater precision with regard to LOI, thus becoming a good alternative to be used as a reference method. In addition, the operability in the laboratory is reflected in the reduction of time and optimization of the human resource. The correlation level shows a low level of significance among these methods, the variation is greater in the DUMAS method (3.38%), due to the analyzed volumes of the samples and the auxiliary equipment level of precision.